Active visfatin is elevated in serum of maintenance haemodialysis patients and correlates inversely with circulating HDL cholesterol - Nuesken, Kai-Dietrich; Petrasch, Maurice; Rauh, Manfred; Stoehr, Wolfgang; Nuesken, Eva; Schneider, Holm; Dötsch, Jörg (Nephrology Dialysis Transplantation, 2009)
Background. Increased circulating visfatin may be associated both with endothelial damage and with increased mortality in end-stage renal disease (ESRD). HDL cholesterol is an independent, strong inverse predictor of cardiovascular events. However, associations between visfatin and parameters of lipid metabolism are unclear. Moreover, serum concentrations of visfatin measured by an enzyme immuno assay (EIA) are conflicting and do not correlate with ELISA (enzyme-linked immunosorbent assay) data, which predominantly detect enzymatically active visfatin.Methods. A total of 74 haemodialysis (HD) patients and 35 control individuals (C) were studied. All subjects (mean age 62.9 years) provided fasted blood samples (HD patients after 66-69 h without dialysis). Circulating visfatin was measured by the ELISA. Body composition was evaluated using waist circumference, skinfold thickness and body impedance analysis. Results obtained by the ELISA were compared with EIA data.Results. Active serum visfatin was increased in HD (5.58 ± 6.50 ngml) versus C 0.97 ± 1.79 ngml, mean ± SD; P < 0.0001 by multiple regression analysis (MRA) independently of plasma glucose, serum insulin, diabetes, HDL cholesterol and body composition. Within the HD group, only plasma HDL cholesterol (4 lower per additional mgdl HDL; P = 0.001) and insulin-treated diabetes mellitus subgroup of n = 18; 119 higher compared with patients without diabetes (n = 40); P = 0.011 were independently (by MRA) associated with active serum visfatin. Visfatin measured by an EIA showed no correlation with ELISA data.Conclusions. Our study provides reliable data on active visfatin in HD patients using a well-characterized ELISA. Loss of renal function is accompanied by increased circulating active visfatin concentrations in our patients. Furthermore, decreased HDL cholesterol may hint at an increased probability of cardiovascular events in HD patients with elevated serum visfatin.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Body composition; Diabetes; End-stage renal disease; HDL cholesterol; Visfatin